Press-konferentsiia vitse-prezidenta Rossii . Press-konferentsiia vitse-prezidenta Rossii . Press-Conference of the Vice-President of Russia . Пресс-конференция вице-президента России - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. The President's speech on the dangers of "dictatorship of democracy." Featured in the program: Rutskoi, Aleksandr Vladimirovich (Vice President of the Russian Academy of Sciences) Речь президента об опасности "диктатуры демократии". В программе участвуют: Руцкой, Александр Владимирович (Вице-президент Академии наук России)